Vliv firemní kultury na výkonnost pracovníků ve společnosti - Ondrůjová, Lenka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
. Výsledkem provedeného průzkumu by měly být návrhy pro společnost a její skutečné uplatnění týkající se zejména etického kodexu, plánu školení, speciálního fondu, individuálního hodnocení a bezpečnosti informací. Závěr práce tvoří realizace a nastavení firemní kultury v nově vzniklé společnosti s cílem zvýšení výkonnosti zaměstnanců.

This diploma thesis deals with the issue of influence of corporate culture on the staff productivity in COMGUARD a.s. company. The result of the survey are propositions for this company and their factual application which concerns mainly the ethical code, a training plan, a special fund, individual assessment, and information protection. The closing part of this diploma thesis includes realization and adjustments of the corporate culture aimed at increased staff productivity
Organizational Culture and its Influence on Managing of the Company
Keywords: Firemní kultura; výkonnost pracovníků; etický kodex; představy; hodnoty; rituály; podniková etika.; Corporate culture; staff productivity; ethical code; concepts; values; rituals; company ethical code